ASSESMEN NASIONAL: SURVEY KESIAPAN - Supriyanto; Dian Rustyawati (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
This study aims to see and analyze the readiness of teachers and students in the National Assessment. The research was conducted with a survey method through the distribution of google form questionnaires. The data obtained were analyzed using descriptive statistics. The results of the study group of students showed that 46.6% of students understood national assessment and 53.2% of students did not understand well about national assessment. This is due to the fact that the education unit has not yet disseminated the implementation of the national assessment which has three instruments including the Minimum Competency Assessment (AKM), learning surveys and learning environment surveys. The results of the teacher group research stated that 75% of teachers understood national assessment and 25% of teachers did not understand national assessment. A national assessment is carried out to evaluate the input, process, and quality of teaching and learning in the classroom so as to improve the quality of Indonesian education.